Bearing capacity assessment of a 14th century arch bridge in Lecco (Italy). Issue 2 (17th February 2018) - Martinelli, Paolo; Galli, Andrea; Barazzetti, Luigi; Colombo, Matteo; Felicetti, Roberto; Previtali, Mattia; Roncoroni, Fabio; Scola, Marcello; di Prisco, Marco
ABSTRACT: The article presents the results of an experimental and numerical investigation on Azzone Visconti bridge, a 14th century arch bridge in Lecco (northern Italy). Starting from the historical data and from an extensive mechanical characterization of both the soil constituting the riverbed and of the masonry constituting the piers, the aim of the study is to investigate the bearing capacity of the bridge. A testing loading scheme defined according to the current Italian Code is adopted to check the structural behavior. A simplified finite element structural model was conceived and calibrated as a control tool to safely perform the experimental tests. Post-test nonlinear finite element analyses have allowed the prediction of the bridge bearing capacity and the definition of the bridge class according to the Italian regulations.